2023
DOI: 10.3389/fmars.2023.1114120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-temperature stress on intestinal structure, enzyme activities and metabolomic analysis of juvenile golden pompano (Trachinotus ovatus)

Abstract: Water temperature plays a crucial role in the growth, survival, and reproduction of fish species, as they make up the majority of aquatic fauna. In this study, the effects of low temperature were studied on the functional state of juvenile golden pompano (Trachinotus ovatus) under low-temperature stress. The study was conducted at 28°C in the control group and 18°C in the cold group for 14 d to determine the intestinal tissue, digestive and antioxidant enzyme activities, and metabolites of juvenile fish. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…In addition, SOD is postulated to serve as the primary mechanism for neutralizing superoxide radicals through its catalytic promotion of the disproportionation of H 2 O 2 [31]. CAT has the ability to scavenge H 2 O 2 in order to mitigate the peroxidation of unsaturated fatty acids within cell membranes [32]. In the present study, it was observed that the activity of SOD and CAT was suppressed, indicating that exposure to NIC hindered the antioxidant capacity.…”
Section: Discussionmentioning
confidence: 48%
“…In addition, SOD is postulated to serve as the primary mechanism for neutralizing superoxide radicals through its catalytic promotion of the disproportionation of H 2 O 2 [31]. CAT has the ability to scavenge H 2 O 2 in order to mitigate the peroxidation of unsaturated fatty acids within cell membranes [32]. In the present study, it was observed that the activity of SOD and CAT was suppressed, indicating that exposure to NIC hindered the antioxidant capacity.…”
Section: Discussionmentioning
confidence: 48%
“…Increased SOD activity in both muscle and liver suggests that posttranslational modifications regulate SOD activity [ 58 ]. SOD scavenges oxygen free radicals in the body, CAT decomposes hydrogen peroxide into water, GPx reduces lipid peroxides to alcohols and tries to minimize the possibility of lipid oxidation and the damage caused by MDA to cells [ 9 ]. In our research findings, it was determined that these three enzymes cooperate to complete the antioxidant process.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, experimental biology is particularly important in understanding the effects of global warming on fish [ 19 , 20 ]. As a result of the sensitivity of physiological parameters and to adapt to temperature changes, fish alter their endocrine processes, metabolic rates, immune and antioxidant systems [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation